Corrosion protection of AA2024 by sol-gel coatings modified with MBT-loaded polyurea microcapsules - Maia, F.
In this work we report the synthesis of polyurea microcapsules loaded with corrosion inhibitor 2 mercaptobenzothiazole (MBT) for corrosion protection of 2024 aluminum alloy. The microcapsules were prepared by interfacial polycondensation. The resulting capsules exhibit spherical shape, with diameter ranging between 100 nm and 2 lm. The loading content of MBT was found to be 5 wt% and release studies showed that MBT is preferentially released under acidic and alkaline conditions and follows a Fickian dif fusion model. This pH dependency seems suitable for protection of metallic alloys where corrosion pro cesses are accompanied by local pH changes. Furthermore, the microcapsules were added to a hybrid sol gel coating and its performance assessed by electrochemical and accelerated standard tests. The results obtained indicate that capsules loaded with MBT do not affect negatively the barrier properties of sol gel coatings, and contribute for the enhancement of adhesion of coatings to the metallic substrate. More rele vant, these additives impart active corrosion protection suppressing corrosion activity at defect sites, which opens prospects for application of polyurea microcapsules as additives for high performance coatings.